Recuperación de tres coberturas forestales de altura media en Costa Rica: análisis de los oligoquetos, el mantillo y suelo Recovery of three tropical forest covers from mid-elevation sites in Costa Rica: oligochaetes, litter and soil analysis - Junior Pastor Pérez-Molina; Roberto A Cordero Solórzano (Revista de Biología Tropical, 2012)
La región Río Macho, un paisaje altamente fragmentado con riesgos inminentes de derrumbes e importantes servicios ambientales, ha sufrido una recuperación parcial de su vocación forestal por reforestación con especies exóticas y regeneración natural. Hemos comparado algunos rasgos del sustrato mediante la combinación del potencial bioindicador de los oligoquetos, rasgos del mantillo y características fisicoquímicos del suelo en tres sitios (bosque secundario viejo, tacotal y plantación Cupressus lusitanica). El bosque presentó la menor densidad de oligoquetos, el menor pH y el mayor contenido de humedad (CA) y fósforo del suelo. Hubo una correlación positiva entre los cocientes de C/N y C/P del mantillo y el pH del suelo, y negativa entre la profundidad, nitrógeno, fósforo del mantillo y fósforo del suelo. Los resultados sugieren que los oligoquetos son sensibles a cambios de los rasgos antes mencionados, que algunos de estos rasgos pueden ser buenos indicadores de la condición actual de regeneración de las coberturas estudiadas, y las coberturas han alcanzado concentraciones de varios nutrientes similares al bosque secundario viejo. Estos estudios a nivel ecosistémico a través de la evaluación de criterios sencillos pueden ayudarnos a inferir rápidamente el estado de algunos de los muchos y complejos compartimentos de los ecosistemas. In Costa Rica, the region of Río Macho is a highly fragmented landscape with imminent risk of landslides. This area, which provides important environmental services, has been partially recovered to its original forest through intentional reforestation with exotic species or natural regeneration after abandonment. The aim of this study was to evaluate the bioindicator potential of oligochaete presence as well as some litter and soil characteristics. The ecosystem recovery of the two common restoration modes was measured within three different forest covers. For this, some substrate characteristics were analyzed and compared in a 50 years old secondary forest, a 13 years tacotal, and a 35 years cypress (Cupressus lusitanica) plantation. The three sites studied differed in density, biomass and average mass of oligochaetes, and in some litter (depth, nitrogen, phosphorus and C/N ratio of litter), and soil variables (soil water content (CA), pH, phosphorus, cation exchange capacity, and magnesium). The forest registered the lowest density of earthworms and soil pH, and the highest soil CA and phosphorus. CA was inversely related to the oligochaete density across sites. Besides, there were positive correlations between C/N and C/P ratios from the litter and soil pH, and inverse correlations of litter depth, litter N and P concentrations with soil P. Discriminant Analysis (AD) performed with all soil and litter variables, produced a sharp classification of the three forest cover types. AD suggests that site differences were mostly determined by soil CA and litter nitrogen concentration. Considering all the evaluated parameters, our results suggest in the first place, that oligochaetes are sensitive to changes in some soil and litter characteristics. Secondly, aside from the striking oligochaete differences between the old secondary forest and the other two sites, some soil and litter traits resulted good indicators of the present recovery of the three forest covers. In addition, comparing soil nutrients content (organic carbon, nitrogen, calcium, potassium and sulfur) among the three sites, our findings indicate that the cypress plantation had reached soil nutrient conditions similar to the old secondary forest, presumably by the accumulation of nutrients, as a result of low nutrient recirculation. In conclusion, ecosystem level studies throughout simple evaluation criteria (soils, oligochaetes and ground litter) can be used as rapid indicators of the state of some of the many and complex forest ecosystem compartments.